Value co-creation with family caregivers to people with dementia through a tailor-made mHealth application: a qualitative study - Aber Sharon Kagwa; Hanne Konradsen; Zarina Nahar Kabir (BMC, 2022)
Abstract Background Digitalization has been recognized as an efficient and cost-effective solution to address the increasing need for care due to the ageing population and the rise in people with dementia. This has subsequently increased the need to also care for family caregivers in community settings. Another benefit of digitalization is the introduction of new service concepts within service-dominant logic namely, value co-creation, which is changing the dynamics in healthcare, transitioning from a provider-centric to a customer-centric approach. The literature indicates that this transition is a slow process in healthcare due to the complex service context consisting of multi-stakeholders, with a fragmented decision-making process. This has resulted in limited research on how individuals co-create value through technology. The study aimed to explore how family caregivers to people with dementia living at home, as consumers of healthcare services co-create value in a multi-stakeholder context through a tailormade mHealth application. Methods A qualitative explorative design was used. Data were collected through semi-structured interviews with 12 family caregivers of people with dementia living at home. The data were analyzed deductively using qualitative content analysis. Results The findings show how family caregivers to people with dementia as healthcare consumers, engaged with a mHealth application and other actors in their service network through different levels of value co-creation activities. Conclusion This paper showed a willingness among family caregivers to people with dementia living at home, who mostly consisted of older people, to implement new technology to assist them with their caregiving tasks. The different value co-creation activities adopted by the family caregivers generated different levels of experiential value such as support, knowledge, and increased access to healthcare.